Determinants of Physical Activity among Older Adults Through Social Ecological Theory: 2021 Community Health Survey - Chul-Woong Lee; Byungmo Ku (Korea Institute of Sport Science, 2024)
PURPOSE This study aimed to analyze factors associated with physical activity (PA) in older adults based on social ecological theory. METHODS Secondary analysis was conducted using raw data from the 2021 Community Health Survey. after excluding 129 non-responses in the PA domain, a total of 74,363 individuals were included in the final analysis. A total of eight factors, including personal (level of depression, history of falls), relational (relationships with neighbors, living alone), community (satisfaction with the local community system, safety), and environmental factors (living environment, natural environment), were selected in accordance with the key points of social ecological theory. To analyze social ecological factors related to the PA of older adults, we conducted a decision tree analysis using Chi-square automatic interaction detection (CHAID). RESULTS The average PA level among older adults was approximately 136 minutes, but the mode and median were both 0 minutes. A total of 20.2% of older adults met the physical activity recommendations, while 79.8% did not. According to the first split of the decision tree, living alone was the most relevant factor associated with the PA of older adults, followed by depression and falls. Older adults living alone, with a depression score of 10 or higher, and who had experienced a fall within the past year, were least likely to meet the PA recommendations. CONCLUSIONS This study urgently suggests that PA programs should target older adults living alone, experiencing depression, and falls.